Perceived playfulness, gender differences and technology acceptance model in a blended learning scenario - Padilla-Meléndez, Antonio; del Aguila-Obra, Ana Rosa; Garrido-Moreno, Aurora (Computers and education, 2013)
The importance of technology for education is increasing year-by-year at all educational levels and particularly for Universities. This paper reexamines one important determinant of technology acceptance and use, such as perceived playfulness in the context of a blended learning setting and reveals existing gender differences. After a literature review on the mentioned topics, some statistical analysis, such as difference between means and structural equation modeling, were run with a sample of 484 students. The main contribution of this study is to provide evidence that there exist gender differences in the effect of playfulness in the student attitude toward a technology and the intention to use it. In females, playfulness has a direct influence on attitude toward using the system. In males, this influence is mediated by perceived usefulness. Some implications and conclusions are included. ► Perceived playfulness and gender differences are reexamined. ► Longitudinal data from 484 undergraduates are analyzed. ► There exist gender differences in attitude and intentions to use. ► In females, playfulness influences attitude toward using the system. ► In males, playfulness influences attitude mediated by perceived usefulness.